Critical Thinking Development in Pharmacy Education: A Meta-Analysis - Michael J Peeters; Kimberly L Zitko; Varun A Vaidya (University of Minnesota Libraries Publishing, 2016)
Objective: The investigators aimed to summarize prior studies of critical thinking development among pharmacy students, using the California Critical Thinking Skills Test (CCTST), Health Sciences Reasoning Test (HSRT), and Defining Issues Test (DIT). Methods: Independently, two investigators (KLZ, MJP) systematically searched available literature using PubMed, Google Scholar, ERIC, PsychInfo, as well as pharmacy education conference abstracts in American Journal of Pharmaceutical Education. Their search terms were 'pharmacy', and ['critical thinking', 'HSRT', 'CCTST', and 'DIT']. Studies included were those that investigated pharmacy students, used one of the tests (CCTST, HSRT, DIT), and used a longitudinal design with test administration at two or more time-points for the same subjects (i.e., development). On review, the CCTST and HSRT seem more foundational to analytical/critical thinking, while the DIT appears to measure moral/complex thinking. Summarizing used meta-analysis with Cohen's d and random-effects modelling. Results: Five studies involved thinking development with 10 separate cohorts for meta-analysis (8 cohorts for CCTST, 2 for DIT, and 0 for HSRT). At 5 institutions, 407 and 1148 students were included (CCTST and DIT, respectively). For the CCTST, the overall effect was 0.33 (0.19-0.47 95%CI) with some heterogeneity among study cohorts (I2=52%). For the DIT, the overall effect was -0.23 (-0.83-0.37 95%CI) with considerable heterogeneity between study cohorts (I2=95%). For the CCTST and DIT, some studies showed effect-sizes greater than 0.5. Meta-analysis of the HSRT could not be conducted (i.e., 0 studies found). Implications: While measuring different aspects of "critical thinking", the CCTST and DIT showed responsiveness to change and appear to be promising measures of cognitive development. These tests should be used in further well-designed research studies that explore strategies for improving cognitive development in pharmacy education. Conflict of Interest We declare no conflicts of interest or financial interests that the we or members of our immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties.   Type: Original Research